Optimizing Energy Efficiency and Indoor Air Quality in Building Design for Hot and Humid Climates - Taemthong Wannawit; Plitsiri Itthi (E3S Web of Conferences)
Optimizing energy efficiency and indoor air quality is essential in hot and humid climates like Thailand, where high energy consumption and poor ventilation are common challenges in air-conditioned spaces. This research presents two case studies that focus on improving energy performance and environmental quality in distinct building types: a commercial building and a university classroom. The first case study investigates energy efficiency in a commercial building by analyzing various door configurations. Experiments conducted in an 18-square-meter room compare the energy consumption of outward-opening doors with air curtains, sliding doors with air curtains, and vestibule doors without air curtains. The results show that sliding vestibule doors without air curtains were the most energy-efficient, while outward-opening doors with air curtains consumed the highest amount of energy, highlighting the importance of door selection in reducing energy use in commercial settings. The second case study examines a university classroom where green walls were integrated to improve indoor air quality and energy efficiency. This study evaluates the impact of both active and passive green wall systems on energy use and CO2 levels in a classroom with 10 occupants. Active green walls (AGW) using Epipremnum aureum plants demonstrated a 35% reduction in CO2 concentrations and a 26% decrease in energy consumption compared to classrooms without green walls. Together, these case studies provide valuable insights for optimizing energy efficiency and indoor environmental quality in commercial and educational buildings, offering practical solutions for reducing energy consumption and enhancing occupant comfort in hot and humid climates.